Mapping the healthcare chaplaincy workforce: a baseline description. Issue 4 (2nd October 2021) - White, Kelsey B.; Barnes, Marilyn J. D.; Cadge, Wendy; Fitchett, George
Abstract: Changing U.S. demographics and the growing emphasis on diversity in the healthcare workforce requires professional healthcare chaplains to examine the characteristics of its own workforce. Previous research suggested that chaplains were mainly Caucasian/White and Mainline Protestant. To explore further, this paper presents a baseline sketch of the workforce and identifies important differences among board-certified chaplains (BCCs), certified educators, certified educator candidates (CECs), and clinical pastoral education (CPE) students. Although missing data quickly became the central story of the analysis and thus requires caution in comparison, the preliminary results suggest BCCs and Certified Educators are older and Whiter/more Caucasian than CECs and CPE students. At least one-third of chaplains and Certified Educators identify as Mainline Protestant, but students and CECs reported greater variation in religious affiliation. Chaplains may be similar to users of healthcare and hospitalized persons in terms of gender and race/ethnicity. Recommendations include suggestions for improving the data infrastructure of professional chaplaincy organizations.